Comparison of 12-Month Outcomes of Kahook Dual Blade Excisional Goniotomy Performed by Attending versus Resident Surgeons - Pratte, Eli L.; Landreneau, James R.; Hirabayashi, Matthew T.; An, Jella A. (Journal of Academic Ophthalmology, 2020)
Objective Kahook Dual Blade goniotomy (KDB) has proven effective in lowering intraocular pressure (IOP) and reducing the medication burden in patients with glaucoma. This study compares outcomes up to 12 months postoperatively after KDB combined with phacoemulsification (phaco-KDB) between an ophthalmology attending and residents.Methods A retrospective analysis was performed on 160 eyes of 113 patients who received a phaco-KDB performed by either an ophthalmology attending or a resident under direct guidance of the attending. Data for each patient was collected preoperatively and at 1 day, 1 week, 1 month, 3 months, 6 months, and 12 months postoperatively. The primary outcome measure was surgical success, defined as 20% IOP reduction or at least 1 medication reduction at 12 months. The secondary outcome measures included mean IOP and medication reduction at each postoperative time point, adverse events, operating time, and survival time, defined as time to failure to meet the criteria for surgical success or requiring a secondary IOP-lowering procedure.Results Preoperative mean IOP was comparable between the two groups (p = 0.585), while baseline medications were higher in the attending group (p = 0.040). Rate of successful outcomes was similar in both groups at 12 months (73.3% attending vs. 87.5% residents, p = 0.708). Mean IOP reduction (1.7 vs. 4.3%, p = 0.278) and medication reduction (0.7 vs. 0.6, p = 0.537) also did not differ at 12 months. Presence of adverse events was similar between the groups (21.6 vs. 27.3%, p = 0.938). The survival time was significantly longer in the attending group (356.3 ± 20.2 days vs. 247.1 ± 26.8 days, p = 0.003). Resident cases took ∼10 minutes longer compared with attending cases (p < 0.001).Conclusion IOP lowering outcomes and rate of adverse events of KDB were similar whether the primary surgeon was an attending or a resident surgeon. The survival time was significantly longer in the attending group, but overall success rate was 77.5% for both groups. This suggests phaco-KDB is an effective procedure that can be safely performed by a trainee under direct supervision of an experienced surgeon.
Keywords: glaucoma; goniotomy; Kahook Dual Blade; KDB; attending; resident; outcomes